Homossexualidade(s) e psicanálise: debates entre os primeiros psicanalistas - Sousa, Allan Ratts de (2020)
In the history of psychoanalysis, since its beginnings, homosexuality is a topic that has been discussed, especially since there is no consensus about an etiology or a unique concept that defines it. Freud has always treated homosexuality as a destination of the sexual drive, arguing that the choice of the same sex as a sexual object does not in itself constitute a pathology, therefore it is not possible to categorize homosexuals as sick. In line with Freud's thinking, some of his contemporaries, such as Sándor Ferenczi and Otto Rank, did not see homosexuality as an impediment to analytical training. Karl Abraham and Ernest Jones, on the other hand, problematized the institutionalization of analysts who declared themselves homosexuals. With that being said, this dissertation makes a survey of the first psychoanalytical conceptions about homosexuality into their literary work and in another documents, such as letters and interviews, by Freud and these cited authors, highlighting points of dialogue between them, always in connection with the relevant events in the history of psychoanalytic movement with regard to its institutionalization and diffusion in the world. Along this path, we could see that homosexuality was, then, conceived by Freud as a plural phenomenon, with different etiologies and varied manifestations, elaborated from his clinical experience and a fruitful debate with his peers, who were not only influenced by Freudian theories, but also influenced them. Finally, we found that the elements of disagreement between Freud and his contemporaries were in the political-institutional directions given to the theorizations in favor of the interests of their groups or institutions. Thus, we conclude that the process of institutionalizing psychoanalysis took place in parallel to these discussions, showing the importance of thinking about the dialogue between psychoanalysis and society, possible, for example, in official places of analytical training, but also in others, such as the university, which emerges as an interesting place for reflection on the theoretical-clinical research of psychoanalysis.